2007
DOI: 10.1002/macp.200600526
|View full text |Cite
|
Sign up to set email alerts
|

Melt Crystallization and Morphology of Poly(p‐phenylene sulfide) under High Pressure

Abstract: The high‐pressure melt‐crystallization behaviors of poly(p‐phenylene sulfide) (PPS) were investigated using WAXD, DSC, TEM and SEM. PPS extended‐chain crystals with c‐axis thickness exceeding 4.5 µm were formed at high pressure. The DSC results showed that the melting temperature and melting enthalpy of high‐pressure crystallized PPS samples were up to 327.53 °C and 94.96 J · g−1, respectively, which were higher than the values of ideal PPS perfect crystals used by some researchers, and the melting enthalpy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Wide-angle X-ray diffraction measurement was performed to determine the crystalline structure of PLA samples, as shown in Figure 3. In the case of high-pressure sample crystallized at 185 o C, besides the strongest diffraction rings appearing at 16 (010) and (015) reflections of the stable α-form of PLA are also observed, apparently different from the normal-pressure sample, where only two strong reflections of (200)/(110) and (203) appear. In addition, the characteristic diffraction peaks at 16.7 o and 19.1 o shift slightly towards higher angles for the high-pressure samples, which demonstrates a closer spacing between the crystal planes and the dense packing of polymer chains in the crystal lattice caused by high pressure.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Wide-angle X-ray diffraction measurement was performed to determine the crystalline structure of PLA samples, as shown in Figure 3. In the case of high-pressure sample crystallized at 185 o C, besides the strongest diffraction rings appearing at 16 (010) and (015) reflections of the stable α-form of PLA are also observed, apparently different from the normal-pressure sample, where only two strong reflections of (200)/(110) and (203) appear. In addition, the characteristic diffraction peaks at 16.7 o and 19.1 o shift slightly towards higher angles for the high-pressure samples, which demonstrates a closer spacing between the crystal planes and the dense packing of polymer chains in the crystal lattice caused by high pressure.…”
mentioning
confidence: 75%
“…The low crystallization temperatures correspond to extremely high degree of undercooling, which is not benefit to the growth of crystals. While if crystallized at a suitable undercooling as a result of high crystallization temperature, the regime III to II transition of Lauritzen-Hoffman theory will induce reorganization and lamellae thickening changes in the crystals, 16 to enhance the crystallinity. Wide-angle X-ray diffraction measurement was performed to determine the crystalline structure of PLA samples, as shown in Figure 3.…”
mentioning
confidence: 99%
“…Lu et al have reported that the higher melting point of PPS is that of crystallized PPS under high pressure . It is likely that the melting point of PPS is higher in this case because of the extended molecular chain of the polymer and the orientation of this chain.…”
Section: Resultsmentioning
confidence: 85%
“…Figure shows the XRD results of PPS/TPU composites. The four diffraction peaks at 18.83, 20.58, 25.62, and 27.42° corresponds to the (110), (200/111), (112) and (211) planes of the orthorhombic structure of PPS, respectively . The PPS/TPU composites show the same diffraction peaks as the pure PPS.…”
Section: Resultsmentioning
confidence: 90%
“…Where Δ H m is the melting enthalpy of PPS in the composites, and Δ H * is the melting enthalpy of perfect crystallization of pure PPS (Δ H * = 94.96 J/G) …”
Section: Methodsmentioning
confidence: 99%